Desain Karakter dalam Buku Ilustrasi sebagai Edukasi Resiko Overthinking bagi Remaja 18-22 Tahun - Dea Salfia Murdiasari; Aninditya Daniar; Diana Aqidatun Nisa (FKIP, Universitas Palangka Raya, 2026)
Overthinking is a state where a person thinks about something excessively or spends a lot of time thinking and analyzing something. Overthinking has been known for a long time, but the term